Witnessing Interparental Violence and Acceptance of Dating Violence as Predictors for Teen Dating Violence Victimization. (April 2016) - Karlsson, Marie E.; Temple, Jeff R.; Weston, Rebecca; Le, Vi Donna
We examined the association between witnessing interparental violence, attitudes about dating violence, and physical and psychological teen dating violence (TDV) victimization. Participants were 918 teens with dating experience. Witnessing interparental violence and acceptance of dating violence were significant predictors of TDV victimization. Acceptance of dating violence was also a partial mediator between witnessing interparental violence and TDV victimization. Witnessing mother-to-father violence and acceptance of female-perpetrated violence were the most consistent predictors. TDV programs aiming to prevent victimization could benefit from targeting youth exposed to father-to-mother and mother-to-father violence, targeting attitudes about violence, and tailoring interventions to gender-specific risk factors.